2022
DOI: 10.1097/cmr.0000000000000807
|View full text |Cite
|
Sign up to set email alerts
|

Uveal melanoma metastatic at initial diagnosis: a case series

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…One patient developed liver metastases as long as 36.7 years after the initial diagnosis of UM. Less than 3% of patients present with metastatic disease at initial diagnosis, which is consistent with our results (4%) 14 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…One patient developed liver metastases as long as 36.7 years after the initial diagnosis of UM. Less than 3% of patients present with metastatic disease at initial diagnosis, which is consistent with our results (4%) 14 …”
Section: Discussionsupporting
confidence: 93%
“…Less than 3% of patients present with metastatic disease at initial diagnosis, which is consistent with our results (4%). 14 Patients with CM had a higher incidence of BRAF mutation (55% vs. 0%, p < 0.001) compared with patients with UM. Tan et al also reported a different BRAF mutant status between UM (8.3%) and CM patients (57.1%) (p = 0.038) in a multi-ethnic Asian cohort.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation